Sistem Pembuktian yang Digunakan Oditur Militer dalam Tindak Pidana Pembunuhan Berencana yang Dilakukan Anggota Militer - Khoiroh, Aimmatul; Firmansyah, Hery (Universitas Ekasakti, 2023)
According to W.L.G. Lemaire, criminal law is law including norms containing obligations and prohibitions stipulated by law, associated with forms of punishment in the form of punishment, namely special suffering. Enforcement is carried out by the military and the authorities in accordance with statutory regulations. The strength of evidence in court decisions in resolving criminal cases is very important for anyone who resolves criminal cases. The strength of evidence really helps investigators in investigating a criminal case because without evidence, a case cannot be resolved quickly. In Article 184 of the Criminal Procedure Code (Criminal Procedure Code) valid evidence is: Witness Statement, expert testimony, Letter, Instructions, Perpetrator's statement. The purpose of this journal is to find out whether the Military Prosecutor's evidence in the criminal act of premeditated murder committed by Military Members in decision Number 22-K/PMT.II/AD/II/2022 is in accordance with article 172 Paragraph (1) of Law Number 31 of 1997 On Military Justice. This research is normative legal research that is descriptive analysis. Using primary legal materials and secondary legal materials. With an empirical juridical approach. The types and sources of legal materials used are primary legal materials and secondary legal materials. Legal material collection techniques are primary data and secondary data. The legal material analysis technique uses an inductive qualitative method. The research results show that efforts to prove the criminal act of premeditated murder have used valid evidence in accordance with Article 172 Paragraph (1) of Law Number 31 of 1997 concerning Military Justice, namely Witness Statements, Expert Statements, Defendant Statements, Letters.